La simultaneidad de voces como recurso de confrontación ideológica en el libro “Tromba de Agosto” de Jorge Pimentel - Guzmán Rodríguez, Joe Carlomelvin (2017)
The present thesis aims to demonstrate that the ideological confrontation of socialism and capitalism in the poemario "Tromba de Agosto" by Jorge Pimentel is achieved through the use of the lyric resource of the simultaneity of voices._x000D_ The methodology used to obtain the results of poetic analysis consists of the polyphony of enunciation as a theatrical representation proposed by Oswald Ducrot, where it is explained that to obtain a more accurate and efficient analysis of a literary discourse, it is necessary to divide it in three elements: the empirical subject - the real author of the discourse - the speaker - the supposed responsible of the discourse - and the enunciators - voices or points of view that are introduced in the discourse._x000D_ In the same way, an analysis was made of the characteristics and perspectives of the characters that appear in the poemario, and that define the socialist and capitalist ideologies. In this way we obtain the results that will allow us to know the problematic of the ideological confrontation between two opposing social classes, managing to define the poems as dialogical discourses._x000D_ Finally, the importance of the poem "Tromba de Agosto" in the national poetic scene is highlighted, as Jorge Pimentel represents the voice of the new social subjects that appear marginalized in the Peruvian stage of the second half of the 20th century.